Methionine cycle-dependent regulation of T cells in cancer immunity - Zhao, Tian; Lum, Julian J. (Frontiers in Oncology, 2022)
The methionine cycle comprises a series of reactions that catabolizes and regenerates methionine. This process is crucial to many cellular functions, including polyamine synthesis, DNA synthesis, redox balance, and DNA and histone methylation. In response to antigens, T cells activate the methionine cycle to support proliferation and differentiation, indicating the importance of the methionine cycle to T cell immunity. In cancer, T cells serve as important effectors of adaptive immunity by directly killing cancerous cells. However, the tumor microenvironment can induce a state of T cell exhaustion by regulating the methionine metabolism of T cells, posing a barrier to both endogenous T cell responses and to T cell immunotherapy. Here we review the role of methionine cycle metabolites in regulating the activation and effector function of T cells and explore the mechanism by which tumor cells exploit the methionine pathway as a means of immune evasion. Finally, we discuss new perspectives on reprograming the methionine cycle of T cells to enhance anti-tumor immunotherapy.